Quantifying Per-Cell Chlorophyll a in Natural Picophytoplankton Populations Using Fluorescence-Activated Cell Sorting - Bock, Nicholas; Subramaniam, Ajit; Juhl, Andrew R.; Montoya, Joseph; Duhamel, Solange (Frontiers in Marine Science, 2022)
Marine phytoplankton play a central role in global biogeochemical cycling, carbon export, and the overall functioning of marine ecosystems. While chlorophyll a (Chl a) is widely used as a proxy for phytoplankton biomass, identifying the proportion of Chl a attributable to different phytoplankton groups remains a major challenge in oceanography, especially for the picophytoplankton groups that often represent the majority of phytoplankton biomass in the open ocean. We describe a method for measuring picophytoplankton per-cell Chl a in field samples using fluorescence-activated cell sorting followed by solvent-based Chl a extraction and fluorescence quantification. Applying this method to surface samples from the Gulf of Mexico, we determined per-cell Chl a to be 0.24 ± 0.07, 0.6 ± 0.33, and 26.36 ± 20.9 fg Chl a cell-1 for Prochlorococcus, Synechococcus, and PPE, respectively (mean ± SD). Measurements of per-cell Chl a using this method are precise to within 1.7, 2.1, and 3.1% for Prochlorococcus, Synechococcus, and PPE, respectively. We demonstrate that this approach can be used to obtain estimates of group-specific Chl a for Prochlorococcus, Synechococcus, and picophytoeukaryotes, the latter two of which cannot be captured by existing methods. We also demonstrate that measurements of per-cell Chl a made using this method in field samples are sufficiently precise to capture relationships between per-cell Chl a and cytometer red fluorescence, providing a bridge between biomass estimates from cell counts and bulk measurements of total Chl a.